2020
DOI: 10.1021/acsomega.0c03820
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Leaf Stomata and Their Relationship with Photosynthesis in Saccharum officinarum Under Drought and Silicon Application

Abstract: Silicon (Si) plays an important role in the sustainable agriculture industry. The increasing demand for crop production with a significant reduction of synthetic chemical fertilizers and pesticide use is a big challenge nowadays. The use of Si has been proven to be an environmentally sound way of enhancing crop productivity by facilitating plant growth and development through either a direct or indirect mechanism, especially in tropical and subtropical regions. In particular, it has been investigated for its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 68 publications
(129 reference statements)
6
35
0
3
Order By: Relevance
“… 6 , 12 , 54 Limited water irrigation levels could significantly downregulate sugarcane photosynthesis and productivity. 18 , 55 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 , 12 , 54 Limited water irrigation levels could significantly downregulate sugarcane photosynthesis and productivity. 18 , 55 …”
Section: Discussionmentioning
confidence: 99%
“… 17 , 20 , 21 The closure of stomatal openings is an initial effect to limited irrigation and an efficient way to decrease the loss of water when stress is not too severe; however, it limits carbon dioxide diffusion in the plant leaves for photosynthetic capacity. 18 , 22 , 23 The requirement of water under field conditions has been a serious issue since most agricultural areas suffer from seasonal water stress conditions. 4 , 10 , 24 …”
Section: Introductionmentioning
confidence: 99%
“…Improving the inorganic phosphorus content will promote the synthesis of ATP needed in the CO 2 assimilation cycle [48]. In photosynthetic reactions, more work is needed to disclose the significant of Si because very little is known on Si′s role in diurnal variations in plant photosynthetic efficiency [34].…”
Section: Siliconmentioning
confidence: 99%
“…Chen et al [28] indicated that Si-mediated enhancement of leaf gas exchange ability in Oryza sativa plants during water-stressed was correlated with stomatal and nonstomatal variables. Gong and Chen [33] and Verma et al [34] demonstrated the diurnal variations of photosynthetic traits in wheat and sugarcane plants subjected to water stressed conditions with loss in stomatal conductance. However, Si enhanced the photosynthetic efficiency during day time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation